Optimization and numerical investigation of the effect of wall conduction and magnetic field on the nanofluid flow inside a three-dimensional enclosure using the lattice Boltzmann method. Issue 6 (3rd June 2023) - Khan, Farhan; Xiao-Dong, Yang; Aamir, Nudrat; Saeed, Tareq; Ibrahim, Muhammad
Abstract: The LBM is used to investigate three-dimensional nanofluid (NFs) flow inside a square enclosure with a heat source in this research. The heat source is located in the enclosure's middle and operates at a high temperature. The sidewalls have a thickness, leading to heat transfer (HE-TR) from the sidewalls that are at low temperatures to the internal fluid due to their thermal conductivity. An inclined magnetic field (MF) uniformly affects the fluid flow. The effect of parameters such as Rayleigh number (Ra), thickness and thermal conductivity of the sidewall, dimensions of the heat source, Hartmann number (Ha), the volume fraction of nanoparticles (φ), and the angle of the MF on two- and three-dimensional field flow and HE-TR is investigated. Optimization is made on the parameters for maximum HE-TR. The lattice Boltzmann method has been used to simulate nanofluid flow. The results show that an enhancement in the Ha and the angle of the MF reduces the amount of HE-TR. HE-TR is improved by increasing the thermal conductivity of thick walls. The quantity of HE-TR is increased when nanoparticles are added to water.